Symbolic action methods: how systemic team consultation can help to strengthen the self-concept of teams and foster team cohesion - Schweitzer, Jochen; Drews, Antonia (Journal of family therapy, 2020)
This article describes a workshop format including three symbolic action methods, i.e. the ‘who is who sculpture’, the ‘walking through a team’s history’ technique and the ‘speech chorus’ for use in systemic team consultation. The described action methods are suited for work with large teams and small organisations. They help team members to quickly understand their internal diversity and develop a joint sense of the team’s history, hence strengthening the team’s self-concept and fostering team cohesion. Teams are thereby enabled to find ways out of experienced states of collective depression or anxiety. If combined with large group approaches such as appreciative inquiry or open space (Owen, 2000), such a workshop can help teams and organisations to move from their present situation towards a shared vision for a desired future. The workshop and its methods have been carried out and evaluated in many systemic therapy teams and small clinical and welfare organisations in Germany, China and the UK, as well as at conference workshops in the US and Russia. Practitioner points Three Tools to “make teams and small organizations swing” Integrated into a one-day- workshop fostering systemic organizational self reflection Conducted in Germany, China, Russia, the US and the UK